The Influence of IMF By on the Bow Shock: Observation Result. Issue 3 (14th March 2018) - Wang, M.; Lu, J. Y.; Kabin, K.; Yuan, H. Z.; Liu, Z.‐Q.; Zhao, J. S.; Li, G.
Abstract: In this study we use the bow shock crossings contained in the Space Physics Data Facility database, collected by four spacecraft (IMP 8, Geotail, Magion‐4, and Cluster1) to analyze the effect of the interplanetary magnetic field (IMF) B y component on the bow shock position and shape. Although the IMF B z component is usually considered much more geoeffective than B y, we find that the dayside bow shock is more responsive to the eastward component of the IMF than the north‐south one. We believe that the explanation lies in the changes that the B z component induces on the magnetopause location and shape, which largely compensate the corresponding changes in the dayside bow shock location. In the tail, we find that the bow shock cross section is elongated roughly in the direction perpendicular to the IMF direction, which agrees with earlier modeling studies. Key Points: The dayside bow shock is more responsive to the eastward component of the IMF than to the north‐south one As the eastward B y increases, the bow shock standoff distance increases, while the flaring angle decreases The BS tail's cross section is elongated roughly in the direction perpendicular to the IMF, which agrees with earlier modeling studies